1998
DOI: 10.1177/000331979804900607
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Three Different Formulas for Doppler Estimation of Pulmonary Artery Systolic Pressure

Abstract: Noninvasive pulmonary artery systolic pressure (PASP) is calculated by summing the right ventricular systolic pressure obtained from Doppler velocity of regurgitant flow through the tricuspid valve and the right atrial (RA) pressure. The RA pressure is generally assumed from different formulas. An accurate RA pressure estimation will add precision to PASP calculation. One of the methods to estimate RA pressure is the inferior vena cava collapsibility index (IVCCI). In 45 patients referred for right heart cathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…The I 2 statistic was 99% (95% CI 88 to 99) indicating significant heterogeneity between the studies. Subgroup analysis for studies with a mean sPAP of 50 mm Hg or less revealed a summary correlation of 0.65 (95% CI 0.61 to 0.69; n=12)30 31 33 35 36 39 42 43 45–47 54 and for studies with a mean sPAP greater than 50 mm Hg, 0.71 (95% CI 0.65 to 0.77; n=8) 38 41 48–50 52 53 56. Egger's test revealed significant publication bias (p<0.001), which was consistent with an asymmetrical funnel plot with missing studies in the lower left and upper right (figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…The I 2 statistic was 99% (95% CI 88 to 99) indicating significant heterogeneity between the studies. Subgroup analysis for studies with a mean sPAP of 50 mm Hg or less revealed a summary correlation of 0.65 (95% CI 0.61 to 0.69; n=12)30 31 33 35 36 39 42 43 45–47 54 and for studies with a mean sPAP greater than 50 mm Hg, 0.71 (95% CI 0.65 to 0.77; n=8) 38 41 48–50 52 53 56. Egger's test revealed significant publication bias (p<0.001), which was consistent with an asymmetrical funnel plot with missing studies in the lower left and upper right (figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…14 -17 Right ventricular systolic pressure (RVSP) was estimated from the tricuspid regurgitant velocity with the modified Bernoulli equation: 4ϫ(velocity) 2 ϩ10 mm Hg for right atrial pressure. 18,19 The use of 10 mm Hg for estimation of right atrial pressure provides a consistent estimation of RVSP across a broad spectrum of patients referred for echocardiography and compares favorably with hemodynamic measurements. 18 -20 Right ventricular (RV) function was assessed by fractional area change of RV area in the apical 4-chamber view.…”
Section: D Echocardiographymentioning
confidence: 99%
“…15 The peak instantaneous pressure gradient of Tricuspid Regurgitation (TR) was determined from the maximal continuous-wave Doppler velocity and the simplified Bernoulli equation (Abaci et al). 16 RESULTS  Out of the total 138 cases, 84 (60.86%) were sickle cell trait (AS) and 54 (39.14%) were sickle cell disease (SS).  RV-EDA was significantly higher in SS subjects compared to AS subjects (p < 0.0001).…”
Section: Methodsmentioning
confidence: 99%